Myth and reality on human rights at sea in the era of globalization - Cui, Zhipeng; Cao, Xingguo; Zhang, Pengfei (Frontiers in Marine Science, 2025)
The twenty-first-century maritime sector, shaped by globalization, technological advances, and economic shifts, faces persistent gaps in safeguarding seafarers’ rights. Despite international efforts like the ILO’s Maritime Labor Convention 2006, their effectiveness is undermined by the industry’s polycentric governance, weak compliance mechanisms, and the isolated nature of seafaring profession. Through a review of regulatory gaps and case studies, it demonstrates how current standards fall short in practice, arguing that their decentralized structure and weak implementation fail to address systemic risks. This study proposes supplementary measures to strengthen accountability and compliance, emphasizing the need for coordinated action to protect seafarers in an increasingly deregulated industry.